Makna Persekutuan Gerejawi dalam Budaya Tenun Ikat Masyarakat Sikka-Maumere, Flores - Botu, Firgianus; De, Emanuel; Mitan, Magnus (Perspektif, 2020)
This article attempts to interpret the weaving culture of Sikka-Maumere, Flores, in a Christian way. First of all, the weaving tradition is described as a cultural heritage which has social, economic, artistic and religious meanings. It takes a long process and involves many people to create this beautiful woven cloth that is characteristic of the local community in Sikka-Maumere. The process of working on it and its completion can be interpreted in a Christian way, especially from the perspective of an ecclesiastical community. Like the work of weaving, life in an ecclesiastical community requires integrated cooperation between the various parties and a constructive rigor, because the life of an ecclesiastical communion can be compared to the work of weaving. All members of the Church are called to share in this work of weaving together with the main weaver, namely the Lord God Himself.